The impact of institutional investors on real and accrual earnings management around IPO: evidence from Malaysian emerging market - Kalgo, Sani Hussaini; Amin Noordin, Bany Ariffin; Nahar, Hairul Suhaimi; Turmin, Siti Zaidah (Malaysian Finance Association, 2015)
The study examines whether Malaysian IPO firms engage in real and accrual earnings management and determines the impact of institutional ownerships on the earnings management discretionary behaviour. The modified Jones (1991) and Roychowdhury (2006) models were used to investigate accrual and real activity behaviours. Institutional ownerships were classified into Conservative and Neutral Pressure Groups. The results indicate Malaysian IPO firms engage in both real and accrual earnings around IPO corporate event. The multivariate analysis shows institutional shareholders constrain real and accrual earnings management which supports the various regulatory r eforms by Securities Commission and Bursa Malaysia. The study suggests the need to encourage the Neutral Pressure Group of institutional investors to engage more in shareholders activism in order to safeguard the value of their investments and for investors to examine real activity behaviours in making their investment strategy while standard setters and regulatory agencies need to enforce additional measures to constrain real activity discretionary behaviour.